Active crop canopy sensors improve nitrogen use efficiency in dryland maize - Kortbein, Samantha L.; Bathke, Katie J.; Luck, Joe D.; Puntel, Laila; Thompson, Laura J.; Balboa, Guillermo R. (Frontiers in Agronomy, 2026)
Active canopy crop sensor commercialization offers producers the ability to vary nitrogen applications in real time based on crop reflectance measures. However, adoption of active canopy crop sensors has been limited due to inconsistent results, potential yield losses, and lack of information from field-scale trials under different management strategies. Therefore, the purpose of this study was to evaluate the capability of active crop canopy sensor system (OptRx™, Ag Leader, Ames, IA) in field trials on nine non-irrigated maize (Zea mays L.) sites in eastern Nebraska, where rainfall often limits yield (2019–2020). The sensor-based N management treatments were compared to each site’s grower treatment, examining the effects of N base rate, in-season application timing, and spatial variability technology performance. The sensor-based N management reduced N application by an average of 38.7 ± 20.8 kg Nha-1 without a yield penalty in 77% of the sites (n = 9). The base rate of N applied prior to the in-season, sensor-based application rate in-season, and timing of the in-season application influenced the N use efficiency (NUE) of the sensor-based N management approach. Partial factor productivity of N was improved by 16.8 ± 8.4 kg grain kg N−1 relative to growers’ current management. In terms of profit, 35% of sites demonstrated a profit advantage in sensor-based treatments. Field-scale research demonstrates that active canopy sensors can improve nitrogen management efficiency and profitability. These findings highlight the importance of evaluating active canopy crop sensors under variable field conditions to optimize sensor-based N management strategies.